Leading in change : implications of school diversification for school leadership preparation in England and the United States - Storey, Valerie Anne (Emerald Publishing Limited : Information Age Publishing, Inc., 2019)
"Leading in Change : Implications for School Leadership Preparation in England and the United States considers the ways in which school leadership, and its preparation has changed and developed in response to a rapidly changing educational scenario over the last decade. Drawing together leading thinkers, researchers, and practitioners in the field of school leadership and management this text takes an international perspective to consider what we know about school diversification, and school leadership preparation. Theoretically and conceptually informed, the contributors' draw on recent empirical research studies and practitioner experience into school leadership preparation to examine how neoliberal and neoconservative policies are working in unison to privatize and corporatize public schools. It looks at how these policies have impacted the preparation of school leaders. In addition to information, critique, and analysis, multiple perspectives are provided that readers can draw upon to ensure that aspiring school leaders are successfully prepared to lead in a diversified and corporate school context"--